1998
DOI: 10.1038/26246
|View full text |Cite
|
Sign up to set email alerts
|

Amino-acid transport by heterodimers of 4F2hc/CD98 and members of a permease family

Abstract: Amino-acid transport across cellular plasma membranes depends on several parallel-functioning (co-)transporters and exchangers. The widespread transport system L accounts for a sodium-independent exchange of large, neutral amino acids, whereas the system y(+)L exchanges positively charged amino acids and/or neutral amino acids together with sodium. The molecular nature of these transporters remains unknown, although expression of the human cell-surface glycoprotein 4F2 heavy chain (h4F2hc; CD98 in the mouse) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
469
1
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 507 publications
(503 citation statements)
references
References 21 publications
29
469
1
4
Order By: Relevance
“…Similar transport properties were reported for the rat homologue TA1 [8]. We showed that XAmAT-L-lc and h4F2hc form a heterodimer (AmAT-L) that migrates as a band of approximately 120 kDa on SDS-PAGE in non-reducing conditions and that, in the presence of a reducing agent, additional bands of 80 kDa and 40 kDa appear, indicating that heavy and light chains are linked by a disul¢de bond [7]. SPRM1, a Schistosoma mansoni membrane protein with 40% identity to XAmAT-L-lc was also shown to heterodimerize with h4F2hc.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar transport properties were reported for the rat homologue TA1 [8]. We showed that XAmAT-L-lc and h4F2hc form a heterodimer (AmAT-L) that migrates as a band of approximately 120 kDa on SDS-PAGE in non-reducing conditions and that, in the presence of a reducing agent, additional bands of 80 kDa and 40 kDa appear, indicating that heavy and light chains are linked by a disul¢de bond [7]. SPRM1, a Schistosoma mansoni membrane protein with 40% identity to XAmAT-L-lc was also shown to heterodimerize with h4F2hc.…”
Section: Introductionsupporting
confidence: 82%
“…2A shows the SDS-PAGE analysis of immunopreciptiations made with the anti-h4F2hc antibody. The expected band of 80 kDa appeared in oocytes expressing h4F2hc only (lanes 1, 2, 11, 12), and, in contrast, no protein was precipitated when oocytes were injected with either of the light chains alone (lanes 3, 7, 13, 17) [7]. In non-reducing conditions, coinjection of h4F2hc/XAmAT-L-lc or h4F2hc/SPRM1 resulted, as previously shown, in the appearance of a band at V120 kDa, which corresponds to a heterodimer (lanes 14, 18).…”
Section: Coimmunoprecipitation Of Heavy and Light Chains Dependsmentioning
confidence: 97%
See 1 more Smart Citation
“…30 Importantly, CD98 is the main heterodimerization partner for 6 amino acid transporters, which are dependent on the CD98 heavy chain for their localization and proper function. 23 Among those 6 transporters, the bi-directional transporters LAT-1 and LAT-2 export nonessential glutamine to enable the uptake of essential amino acids, which in turn activate the mammalian target of the rapamycin pathway promoting cell growth and survival. 31 Although biologically active small molecules against CD98-associated light chains have been identified, anti-CD98 antibodies provide another approach to modifying amino acid transport.…”
Section: Discussionmentioning
confidence: 99%
“…L-type amino acid transporter 1 (LAT1) is a neutral amino acid transporter and is essential for the transport of large neutral amino acids [6,7]. It has been shown that LAT1 is overexpressed in some malignant tumor cells such as KB human oral epidermoid carcinoma cells [8], esophageal carcinoma [9], Barrett's adenocarcinoma [10], astrocytic tumors [11,12], lung adenocarcinoma [13], oral cancer [14] and osteogenic sarcoma cells [15].…”
Section: Introductionmentioning
confidence: 99%